(untitled) (Marketing Journal, 2025)
This article examines the impact of digital transformation on enterprise strategic management. Key elements such as strategic analysis, decision -making, planning, competitiveness management, and human capital development were analyzed in the № 1 592 context of digitalization. Digital technologies —including big data, artificial intelligence, CRM, and ERP systems —were treated as tools for achieving strategic objectives. The methodological framework included systems analysis, comparative method, expert e valuation, and case study approach. It was found that under the influence of digital transformation, strategic management becomes more adaptive and data-driven, with a stronger focus on customer orientation.